Os fundamentos político-pedagógicos dos centros exclusivos de educação de jovens e adultos no município de São Paulo - Souza, Thiago Fijos de (2021)
This investigation had as object of study the Youth and Adult Education (as we call EJA), specifically the public policy proposed for this modality of education in the city of São Paulo, through two exclusive educational centers: the Municipal Center for Supplementary Education (CEMES, 1992-2002) and the Integrated Center for Youth and Adult Education (CIEJA, 2003-2017). These centers, organized in different periods and governments, indicate conceptual changes in EJA's municipal policy, responding to the political challenges of each historical time, particularly at the time of the creation of CEMES and its replacement by CIEJA, between 2002 and 2003. Our goal was to understand the political-pedagogical foundations of the municipal policy of youth and adult education that each Center presents. To do so, we analyzed and related these fundamentals in light of the challenges and demands of educational policy at each historical moment, when institutional changes occurred. Methodologically, we have opted for a qualitative approach. In order to know our object of study, we conducted a review of academic literature in the Capes BDTD platform, in the Scielo and Google Academic platforms, with the descriptors: "youth and adult education policies in São Paulo", "CEMES", "CIEJA". We used as research sources data and legislation on EJA produced since the 1990s, documents made available by the Department of Documentary Memory of the Municipal Secretariat of Education of São Paulo (SME-SP) and the State Education Council (CEE-SP) and a set of interviews with professionals who participated in the preparation and/or implementation of each Center's proposal. As a result of this research, we found evidence that the political-pedagogical foundations that based the exclusive centers of EJA had a significant influence of popular education at the time they were conceived, having been removed from this framework when implemented and, in the movement to replace CEMES by CIEJA, the original foundations are being recovered amid political disputes.